Magnitude of Anemia and Hematological Predictors among Children under 12 Years in Odisha, India - Shuchismita Behera; Gandham Bulliyya (Anemia)
Background. Anemia is a wide spread public health problem in India which affects children. The present study evaluates the prevalence of anemia and status of various hematological parameters among children of Khurda district, Odisha. Method. A total of 313 children aged 0–12 years were enrolled for the study which included preschool (0–5 years) and school aged (6–12 years) groups. Hematological indicators were measured by standard procedures, which include red blood cell (RBC) indicators, white blood cell (WBC) indicators, and plasma ferritin. Results. Mean hemoglobin (Hb) of the study population was 10.43±3.33 g/dL and prevalence of anemia was 62%. In this population, boys had a lower mean Hb value than that of the girls. All grades of anemia were higher among school age children than preschool children. Mean plasma ferritin was found to be higher in school age boys than their counterpart girls. The mean level of WBC count was found to be higher among preschool age boys than among the school age boys (p=0.025). Conclusion. The prevalence of anemia was higher with concomitant acute infection among study population, which is a matter of concern. Since the hematological parameters are interrelated with each other as well as with the age and gender, relevant intervention strategy and constant monitoring are needed while providing public health nutrition programs to eradicate anemia.